A qualitative study of Canadian resident experiences with Competency-Based Medical Education (Canadian Medical Education Journal, 2022)
Background: Competency-based medical education (CBME) is an outcomes-based curricular paradigm focused on ensuring that graduates are competent to meet the needs of patients. Although resident engagement is key to CBME’s success, few studies have explored how trainees have experienced CBME implementation. We explored the experiences of residents in Canadian training programs that had implemented CBME.Methods: We conducted semi-structured interviews with 16 residents in seven Canadian postgraduate training programs, exploring their experiences with CBME. Participants were equally divided between family medicine and specialty programs. Themes were identified using principles of constructivist grounded theory.Results: Residents were receptive to the goals of CBME, but in practice, described several drawbacks primarily related to assessment and feedback. For many residents, the significant administrative burden and focus on assessment led to performance anxiety. At times, residents felt that assessments lacked meaning as supervisors focused on “checking-boxes” or provided overly broad, non-specific comments. Furthermore, they commonly expressed frustration with the perceived subjectivity and inconsistency of judgments on assessments, especially if assessments were used to delay progression to greater independence, contributing to attempts to "game the system". Faculty engagement and support improved resident experiences with CBME.Conclusion: Although residents value the potential for CBME to improve the quality of education, assessment and feedback, the current operationalization of CBME may not be consistently achieving these objectives. The authors suggest several initiatives to improve how residents experience assessment and feedback processes in CBME.